Dinamika Kebijakan Sistem Zonasi Pendidikan di Indonesia - Abd. Madjid (Yayasan Azhar Amanaa Yogyakarta, 2023)
The education zoning policy in Indonesia is a new breakthrough by the government for equal distribution of the quality of education in all regions in Indonesia. The existence of an educational dichotomy marked by the labeling of favorite schools causes an imbalance in the distribution of quality and students in Indonesia. The education zoning policy has been in effect since 2017 and has undergone several technical changes in its implementation. This study uses a qualitative method, by applying a literature study model. The data collection is taken by data reduction model, data display, verification, and drawing conclusions. Even though the zoning policy has been in effect since 2017, issues regarding the quality of education and students are still an important area of ​​discussion in the field of education in Indonesia. This is indicated by the imbalance in the number of new students in private schools and public schools as well as changes in the model of implementation of learning programs that have occurred since the zoning policy came into force. Therefore, the Indonesian government needs to improve the existing zoning policy system, so that the main objectives of the educational zoning policy can be properly realized.